Qué significa actuar por un fin? La respuesta de Francisco Suárez en el ms De beatitudine (1579) y en el tratado De ultimo fine hominis (1628) - Colmenarejo Fernández, Rosa (2018)
The influence of the work and teaching of Francisco Suárez (Granada, 1548-Lisbon, 1617) in the shaping of modern thought has been widely studied in areas such as political philosophy and law, metaphysics, and epistemology. However, the moral philosophy of Suarez, in particular that which, as he himself explains, was needed as a basis for his moral theology, has yet to be analyzed. In this paper, we propose to elucidate some aspects of Suarezs theory of human agency final causality. We compare two of his commentaries, from different periods, on the I-IIae of Thomas Aquinas Summa theologiae: the unpublished manuscript De beatitudine (1579) and Suarezs treatise De ultimo fine hominis, the first of five treatises on morality posthumously published by Baltasar Álvares (1628). The question analyzed here, the nature of final causality, is assumed as a heuristic instrument to acquaint readers with both the sources studied and the philosophical import of Suárez doctrine on morality. The findings suggest the following: i) the closeness, still with doubts, of Suárez 1579 commentary to Thomas doctrine of human agency final causality; (ii) in the 1628 commentary, his partial assumption of Thomas doctrine on the role of intellect in free choice, and his clear determination in the assertion that the locus finis is the will. Working with these nuances, we illustrate some connection points that show both how 16th century scholasticism deals with philosophical tradition to explain a new image of man, and how subsequent moral philosophy is influenced by these theories while rejecting their theological foundation.